2021
DOI: 10.1001/jamanetworkopen.2021.29416
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Burden of Child Undernutrition for Smaller Electoral Units in India

Abstract: IMPORTANCEGeographic targeting of public health interventions is needed in resourceconstrained developing countries. OBJECTIVE To develop methods for estimating health and development indicators across micropolicy units, using assembly constituencies (ACs) in India as an example. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study included children younger than 5 years who participated in the fourth National Family and Health Survey (NFHS-4), conducted between January 2015 and December 2016. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Round 6 of NFHS data collection between 2023-2024 is underway, which might be able to provide us with a better picture on the performance of ADP. Using micro-level data recent research has drawn attention to heterogeneity in health and nutrition indicators at sub-district level even at the level of villages based on which researchers have argued for geographical targeting at micro-spatial units [20][21][22] . This provides an opportunity for a program like ADP to capitalize on these research findings by identifying the micro hotspots and targeting these small spatial units within a district for potential improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Round 6 of NFHS data collection between 2023-2024 is underway, which might be able to provide us with a better picture on the performance of ADP. Using micro-level data recent research has drawn attention to heterogeneity in health and nutrition indicators at sub-district level even at the level of villages based on which researchers have argued for geographical targeting at micro-spatial units [20][21][22] . This provides an opportunity for a program like ADP to capitalize on these research findings by identifying the micro hotspots and targeting these small spatial units within a district for potential improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the fourth round of National Family Health Survey (NFHS-4) collected in 2015-16 indicates that percentage of stunted, wasted and under-weight children in a district is as high as 65%, 67% and 47% respectively quite disparate from the national averages of 36%, 21% and 33% respectively. Recent research has drawn attention to heterogeneity in health and nutrition indicators using micro-level data at sub-district level even at the level of villages based on which researchers have argued for geographical targeting at micro-spatial units [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…To create a comparable data set of 33 indicators for the 707 districts of India, we linked the clusters from 2016 NFHS to 707 districts in 2021 NFHS. A spatial join was created between the 2016 GPS-enabled clusters and 2021 NFHS district shape file 31 , 32 , 33 using ArcGIS Pro. 34 This approach allowed us to maintain the saliency of the geometry used in the 2021 NFHS data and does not make any alterations to it.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have found that malnutrition can be reduced by controlling those non-genetic factors so that the heredity cannot be controlled in general [10,11]. Several studies on the nutritional status of children in Bangladesh and India have been carried out independently in both countries [12][13][14][15][16][17]. Most of these studies have limitations because they focus on a specific region, not to the whole population.…”
Section: Introductionmentioning
confidence: 99%